Menimbang Kebijakan Petugas Haji Non-Muslim Dalam Perspektif Efisiensi Birokrasi dan Sensitivitas Keagamaan - Abdillah Reyza Habibie; Abdul Sattar (Jayapangus Press, 2026)
This study examines the policy of involving non-Muslim hajj officers in Indonesia, focusing on the tension between bureaucratic efficiency and the religious sensitivity of the Muslim community. The study is motivated by the new policy of the Ministry of Hajj and Umrah, which permits non-Muslims to serve as hajj officers in specific administrative and technical roles. A qualitative descriptive-analytical approach was employed, combining library research and netnography, utilizing scholarly sources and observing public responses on social media. Findings indicate that while the policy enhances bureaucratic efficiency, it triggers public resistance due to perceived threats to the sanctity of the hajj ritual. The study highlights religious moderation as a framework to balance administrative professionalism with respect for sacred values, emphasizing indicators such as national commitment, tolerance, non-violence, and accommodation of local culture. In conclusion, public policies that are sensitive to religious contexts and accompanied by transparent communication can enhance social legitimacy while maintaining bureaucratic efficiency in hajj management.